Using Pictionary as An Effective Way to Improve Young Learners' Reading Skill on A Procedure Text - Susanti, Lina; Dzulfikri , Dzulfikri; Jamilah, Nur (STAI Miftahul Ula Nganjuk, 2023)
This study aims to see how successful Pictionary is at teaching procedural text. Fifty students from Mojokerto's MA Al-Istiqomah second year participated in this study. This study employed a one-group pretest-posttest design. Field notes were used to collect data, and pupils' reading achievement was determined using the minimum passing score. The current research examines the impact of utilizing Pictionary to increase students' comprehension of process language, particularly in determining primary verbs used in the procedure text. As the research tool, a vocabulary test was conducted. The results demonstrated that applying the Pictionary game approach improved vocabulary attainment. This implies that the Pictionary game approach makes it easier for kids to learn a new language.